Helping Educators Learn Pediatric Pain Assessment and Intervention Needs Program (HELP PAIN): Program Development with Community Partners - Natoshia R. Cunningham; Michelle Adler; Jocelyn Zuckerman; Mallet R. Reid; Sarah C. Love; Kelly Theaker; Steven J. Pierce; Rachel Vandenbrink; Jeanne Paque; Andrea L. Wendling; Judith Arnetz (MDPI AG, 2024)
Background/Objectives: This paper details the development of the Helping Educators Learn Pediatric Pain Assessment and Intervention Needs (HELP PAIN) program. Methods: HELP PAIN is an 8 h live training program for school providers (e.g., school nurses and social workers) to use evidence-based nonpharmacologic pediatric pain management tools. The program's scope reflected the reach of the participating intermediary community organizations, resulting in focused training in rural northwest Michigan due to the Health Department of Northwest Michigan's service in that region and statewide reach due to the broad representation of members from the Michigan Association of School Nurses. Results: We describe the development of the HELP PAIN program, drawing on evidence-based nonpharmacologic (e.g., cognitive behavioral and mindfulness meditation) strategies for pediatric pain management. Conclusions: In partnership with the key community organizations and community partners, we developed, interactively refined, and delivered this training program.